Rates of Psychiatric Treatment Reported by Patients with Borderline Personality Disorder and Other Personality Disorders over 16 Years of Prospective Follow-up - Zanarini, Mary C. (Psychiatr Serv, 2014)
OBJECTIVE: The goal of this study was to delineate the course of 16 treatment modalities reported by 290 patients with borderline personality disorder and 72 with other axis II disorders over 16 years of prospective follow-up. METHODS: Treatment use was assessed at baseline and at eight two-year follow-up periods using a semistructured interview of proven reliability and validity. RESULTS: Patients with borderline personality disorder reported significantly higher rates of use of 12 of the 16 treatment modalities studied. Only individual therapy, intensive individual therapy, couples/family therapy, and ECT were used by roughly the same percentage of patients with borderline personality disorder and those with other axis II disorders. In addition, rates of participation in 13 treatment modalities declined significantly over the first eight years of follow-up for those in both treatment groups. However, the rates of participation in 15 of 16 treatment modalities did not decline significantly over the second eight years of follow-up for those in either study group CONCLUSIONS: The results of this study suggest that rates of treatment use by patients with borderline personality disorder decline significantly over the short and midterm. They also suggest that these rates remain stable or fail to decline further over the longer term.